Molecular dynamics simulation studies on influenza A virus H5N1 complexed with sialic acid and fluorinated sialic acid. Issue 18 (12th December 2019) - Jeyaram, R. A.; Priyadarzini, T. R. K.; Anu Radha, C.; Siva Shanmugam, N. R.; Ramakrishnan, C.; Gromiha, M. Michael; Veluraja, K.
Abstract : Abbreviations: HA Hemagglutinin MD Molecular Dynamics MM-PBSA Molecular Mechanics Poisson–Boltzmann Surface Area NA Neuraminidase NAMD Nanoscale Molecular Dynamic Simulation PMEMD Particle Mesh Ewald Molecular Dynamics RMSD Root-Mean-Square Deviation RMSF Root-Mean-Square Fluctuation SIA sialic acid VMD Visual Molecular Dynamics Communicated by Ramaswamy H. Sarma